Implications of changing domestic policies and globalisation for crop-livestock systems Development in West africa - Williams, Timothy O.; Ehui, Simeon K.; Kormawa, P.M. (International Livestock Research Institute, 2004)
Economic and agricultural policies in West Africa have evolved progressively over the last 20 years. Since the early 1980s, most countries in the region have implemented macroeconomic stabilisation and structural reforms to reverse balance of payments deficits, improve economic growth and reduce the bias against agriculture. Specific policy reforms included devaluation of overvalued exchange rates, reduction of tariff and non-tariff barriers, removal of regulatory controls on input and output markets, and elimination of state-owned marketing boards, subsidies and price controls. The domestic policy environment, while still far from ideal, is now generally considered to be more conducive to agricultural growth and trade. At the same time, changes in the international environment have been much more dramatic. Globalisation, manifested in increased international trade, foreign direct investment and capital flows, is a phenomenon that is likely to assume greater importance in the future. Since crop and livestock products are inherently tradable, globalisation presents new opportunities and challenges. Opportunities exist to find new markets for new products at higher prices and thus increase both employment and incomes, but access to the lucrative markets in the developed countries is cumbersome and complex. The evidence on the policy reforms that have been undertaken in several West African countries is reviewed and their impacts on crop-livestock outputs, prices, food security and incomes summarised. The manner in which changes in the external environment have reinforced or contradicted domestic policy reforms in promoting growth of crop-livestock production and trade are examined. Emerging global agricultural trade issues that are of relevance to countries in the region and that need to be addressed to improve these countries' chances of participation in the new global economy and protect their economies from global market instability are highlighted. Perspectives are offered on future policy research that will provide information needed to develop strategies to improve food security, livelihoods and sustainable growth of crop-livestock systems in West Africa.